2013
DOI: 10.1186/2047-217x-2-13
|View full text |Cite
|
Sign up to set email alerts
|

The role of reporting standards for metabolite annotation and identification in metabolomic studies

Abstract: The application of reporting standards in metabolomics allow data from different laboratories to be shared, integrated and interpreted. Although minimum reporting standards related to metabolite identification were published in 2007, it is clear that significant efforts are required to ensure their continuous update and appropriate use by the metabolomics community. These include their use in metabolomics data submission (e.g., MetaboLights) and as a requirement for publication in peer-reviewed journals (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
251
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(255 citation statements)
references
References 8 publications
2
251
0
2
Order By: Relevance
“…A possible route forward thus implies that each study conducted should describe how each metabolite was annotated, and perhaps even more important, at which certainty level (Creek et al 2014). This is unfortunately seldom the case (Salek et al 2013).…”
Section: Feature Annotationmentioning
confidence: 98%
“…A possible route forward thus implies that each study conducted should describe how each metabolite was annotated, and perhaps even more important, at which certainty level (Creek et al 2014). This is unfortunately seldom the case (Salek et al 2013).…”
Section: Feature Annotationmentioning
confidence: 98%
“…Within these classes, the absolute levels found were 0. 15 The GC-Q-MS method optimized for potato tubers was also applied by the same authors to further study potato tuber metabolism in a metabolite profiling comprehensive assessment of four independent potato genotypes characterized by altered sucrose metabolism [123], and later, in combination with spectrophotometric and LC chromatographic assays, in a comprehensive study of primary metabolism on Lycopersicon esculentum (tomato) leaf and developing fruit tissues [130]. In that study, the application of combined platforms allowed the identification of over 70 primary metabolites that were used for the characterization of the metabolite composition of developing tomato fruit.…”
Section: (I) Primary Metabolitesmentioning
confidence: 99%
“…Since then, great interest in standardizing data associated with large-scale metabolomics experiments has become a general consensus, and data sharing, data standards and workflows for metabolomics are progressively becoming more FAIR-compliant (i.e. findable, accessible, interoperable and reusable) within the metabolomics community [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive and comparative studies between different Dioscorea species could potentially be improved by following Metabolomic Society Initiatives (MSI), (Salek, Steinbeck, Viant, Goodacre, & Dunn, 2013) and community recommendations (Fernie et al, 2011) on reported parameters regarding analytical methods, such as sample storage conditions, e.g., frozen, fresh or freeze-dried materials; saponification or non-saponification of extracts and compound identification parameters. Champagne et al (2010) published the only broad species study of carotenoid composition in Dioscorea to date.…”
Section: Introductionmentioning
confidence: 99%